- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 2,896

$\begin{array}{rr}

x' & = -x - 4y\\

y' & = 3x - 2y

\end{array}$

and initial values are

$x(0) = 20\quad y(0) = 20$

so since $x=-x'-4y$

then

$y'=3(-x'-4y)-2y=-3x'-12y-2y=-3x'-14y$

just seeing if this combined eq is ok....i think y also could have been substituted

$4y=-x-x'$ or $y=-\dfrac{x}{4}-\dfrac{x'}{4}$

then

$y'=-3x'+\dfrac{7x}{2}-\dfrac{7x'}{2}$

not that sure

x' & = -x - 4y\\

y' & = 3x - 2y

\end{array}$

and initial values are

$x(0) = 20\quad y(0) = 20$

so since $x=-x'-4y$

then

$y'=3(-x'-4y)-2y=-3x'-12y-2y=-3x'-14y$

just seeing if this combined eq is ok....i think y also could have been substituted

$4y=-x-x'$ or $y=-\dfrac{x}{4}-\dfrac{x'}{4}$

then

$y'=-3x'+\dfrac{7x}{2}-\dfrac{7x'}{2}$

not that sure

Last edited: